机构综合的超混沌相乘求解方法研究 - 何哲明; 罗佑新; 车晓毅; 徐静蓉; 汪超 (Jixie chuandong)
The discovery of dynamical hyper chaos is one of the main achievements in the modern science and how to expand its application has important significance to the development of modern science. Many questions in natural science and engineering are transformed into nonlinear equations to be found,Newton iterative method is an important technique to one dimensional and multidimensional variables and iterative process exhibits sensitive dependence on initial guess point. The regularity of multiplication hyper chaos maps is investigated. The simulations are work out with Matlab software. For the first time,a new method to find all solutions based on utilizing multiplication hyper-chaotic sequences to obtain locate initial points to find all solutions of the nonlinear questions is proposed. The numerical example in linkage synthesis shows that the method is correct and effective. This provides a simple realization method for mechanics design.